2004
DOI: 10.1021/jm030420+
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Embelin as a Cell-Permeable, Small-Molecular Weight Inhibitor of XIAP through Structure-Based Computational Screening of a Traditional Herbal Medicine Three-Dimensional Structure Database

Abstract: The X-linked inhibitor of apoptosis (XIAP) is a promising new molecular target for the design of novel anticancer drugs aiming at overcoming apoptosis-resistance of cancer cells to chemotherapeutic agents and radiation therapy. Recent studies demonstrated that the BIR3 domain of XIAP where caspase-9 and Smac proteins bind is an attractive site for designing small-molecule inhibitors of XIAP. Through computational structure-based screening of an in-house traditional herbal medicine three-dimensional structure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
267
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(284 citation statements)
references
References 62 publications
14
267
2
Order By: Relevance
“…Additionally, we found dose-dependent down-regulation in XIAP expression upon emodin treatment and the knockdown of XIAP by siRNA abrogated the sensitization effect of emodin on TRAILinduced apoptosis in HCC cells. Similarly embelin, a natural XIAP inhibitor [48] has been found to enhance TRAILinduced apoptosis in pancreatic cancer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found dose-dependent down-regulation in XIAP expression upon emodin treatment and the knockdown of XIAP by siRNA abrogated the sensitization effect of emodin on TRAILinduced apoptosis in HCC cells. Similarly embelin, a natural XIAP inhibitor [48] has been found to enhance TRAILinduced apoptosis in pancreatic cancer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…Embelin, a major constituent of embelia ribes, is a cellpermeable, small molecular inhibitor of XIAP. 17 Embelin has been shown to have anti-tumor, anti-inflammatory, and analgesic properties. 30 Our study showed that embelin counteracted the glucose-related stimulatory effect on the proliferation and production of VEGF in Mü ller cells, supporting the use of embelin in the treatment of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Embelin is a small molecule that specifically inhibits XIAP. 17 Mü ller cells were incubated with various concentrations of embelin in the presence of high-glucose conditions (50 mM), and the viable cells were determined by the MTT assay. The results showed that embelin reversed the pro-proliferative effect of highglucose conditions in a dose-dependent manner (Figure 1c).…”
Section: Embelin Reversed the Proliferation And Protein Expression Almentioning
confidence: 99%
“…However, it is not clear whether blocking BIR2 to mediate release of effector caspases, or selectively targeting the BIR3 domain, which binds to inhibit the upstream initiator protease caspase-9, is the more effective strategy (Srinivasula et al, 2001a;Nikolovska-Coleska et al, 2004;Sun et al, 2006). It has been shown in H460 cells that disruption of XIAP -caspase-9 binding with SMAC mimetics restored apoptosis (Yang et al, 2003).…”
Section: A549mentioning
confidence: 99%